The Relationship Between Physical Activity and Limited Range of Motion in the Older Bedridden Patients. - Chiaki Murata; Hideki Kataoka; Hideki Aoki; Shunpei Nakashima; Koichi Nakagawa; Kyo Goto; Junichiro Yamashita; Seima Okita; Ayumi Takahashi; Yuichiro Honda; Junya Sakamoto; Minoru Okita (Canadian Geriatrics Journal, 2023)
Background The purpose of this study is to examine the association between physical activity and contracture in older patients confined to bed in long-term care (LTC) facilities. Methods Patients wore ActiGraph GT3X+ for 8 hours on their wrists, and vector magnitude (VM) counts were obtained as the amount of activity. The passive range of motion (ROM) of joints was measured. The severity of ROM restriction classified, as the tertile value of the reference ROM of each joint, was scored 1-3 points. Spearman's rank correlation coefficients (Rs) were used to measure the association between the VM counts per day and ROM restrictions. Results The sample comprised 128 patients with a mean (SD) age of 84.8 (8.8) years. The mean (SD) of VM was 84574.6 (115195.2) per day. ROM restriction was observed in most joints and movement directions. ROMs in all joints and movement directions, except wrist flexion and hip abduction, were significantly correlated with VM. Furthermore, the VM and ROM severity scores showed a significant negative correlation (Rs = -0.582, p < .0001). Conclusions A significant correlation between the physical activity and ROM restrictions indicates that a decrease in the amount of physical activity could be one of the causes of contracture.